ETHICAL PROBLEMS RELATED TO LANGUAGE PRACTICE IN ISLAMIC PERSPECTIVE - HAPPY SRI REZEKI PURBA (IAIN Padangsidimpuan, 2017)
In this recent year, the problems that related to Ethical aspect increased significantly including in Language Practice. But ethical aspects are not always clear cut; there are many grey areas that need to be threaded with care by organ religions approach. The writer believes that it is important to understand the ethical problem related to language from Islamic Perspective. Because Islam is the truly faith that can answer all of human’s problem. This article aims, first, to identify and classify ethical problems related to language practices and second, to explain the Islamic perspective of ethic including in language practice. The theory of ethics in general and in Islamic perspective also appeared to support the content of this article. Furthermore, the writer hopes that this article can be useful for people who want to study about language practice and ethical problem in Islamic perspective especially